ANALYSIS OF THE IMPLEMENTATION OF E-TENDER PRE-DIPA PROCUREMENT OF GOODS/SERVICES AT THE GENERAL BUREAU OF THE SECRETARIAT GENERAL OF THE MINISTRY OF HEALTH - Rulandari, Novianita; Supriadi, Kenang (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the Implementation of the Pre-DIPA e-tender for Procurement of Goods/Services at the General Bureau of the Secretariat General of the Ministry of Health so that it is hoped that appropriate steps can be formulated in implementing the Pre-DIPA e-tender, problems and efforts made by Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services. The research method used in this research is quantitative research. The sampling technique uses data sources from 5 informants. Data collection techniques in this study used observation, interview, and documentation techniques. This research procedure includes the stages before in the field, while in the field, and data analysis. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. Based on the results of the research, leadership factors, quality of human resources, planning and management, policies and regulations, system integration, and infrastructure and standardization it can be concluded that the implementation of the e-tender pre-DIPA Procurement of Goods/Services at the General Bureau has been going quite well, there are still problems with server down due to frequent maintenance or updating of the system from LKPP. The suggestion is to communicate more intensively with LKPP to reduce server disturbances.